Vibration Analysis of a Payload connected to Quadrotor-type UAV by SMA Spring - Geronel, Renan S. [UNESP]; Bueno, Douglas D. [UNESP]; Botez, Ruxandra M. (American Institute of Aeronautics and Astronautics (AIAA), 2022)
Unmanned Aerial Vehicles (UAVs) have the ability to carry different payloads, and sensors. However, in the presence of any onboard component or attachment load, the UAV dynamics is changed, and its performance can be negatively impacted due to excessive vibrations. The mathematical model of the UAV with a vibrating payload attached to its body is here obtained and presented. The physical connection between the UAV and its payload is assumed to be elastic, and the SMA spring is used for its representation. This SMA spring has the ability to vary its stiffness and damping, by enabling to decrease the undesired vibration (mainly provoked by external disturbances) transmitted to the payload. Numerical simulations are presented, and their results show that this type of configuration considers an interesting strategy for vibration suppression during the flight.